2010
DOI: 10.1002/humu.21374
|View full text |Cite
|
Sign up to set email alerts
|

MET mutations in cancers of unknown primary origin (CUPs)

Abstract: Cancer of unknown primary origin (CUP) defines metastatic disease of unknown origin, accounting for 3–5% of all cancers. Growing evidence demonstrates that inappropriate execution of a genetic program named “invasive growth,” driven by the MET oncogene, is implicated in the metastatic process. MET activation in cancers is mainly consequent to overexpression, whereas mutations are rarely found. We reasoned that the occurrence of MET somatic mutations might sustain premature occult dissemination of cancer cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 39 publications
1
57
0
2
Order By: Relevance
“…Previous studies have reported some activating mutations of c-MET in non-small-cell lung cancer, hereditary and spontaneous renal carcinomas, hepatocellular carcinomas, gliomas, gastric, squamous cell carcinoma of the head and neck, and breast cancers. [41][42][43][44][45][46] Potentially oncogenic mutations involve mainly: (1) point mutations that generate an alternative splicing encoding a shorter protein that lacks exon 14, which encodes for the juxtamembrane domain of c-MET 43,47 ; (2) point mutations in the kinase domain that render the enzyme constitutively active 44 ; and (3) Y1003 mutations that inactivate the Cbl-binding site leading to constitutive c-MET expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported some activating mutations of c-MET in non-small-cell lung cancer, hereditary and spontaneous renal carcinomas, hepatocellular carcinomas, gliomas, gastric, squamous cell carcinoma of the head and neck, and breast cancers. [41][42][43][44][45][46] Potentially oncogenic mutations involve mainly: (1) point mutations that generate an alternative splicing encoding a shorter protein that lacks exon 14, which encodes for the juxtamembrane domain of c-MET 43,47 ; (2) point mutations in the kinase domain that render the enzyme constitutively active 44 ; and (3) Y1003 mutations that inactivate the Cbl-binding site leading to constitutive c-MET expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data suggest that this is unlikely to be the case. In a limited number of tumour cells featuring genetic lesions of MET -caused by gene amplification and, possibly, point mutations 23,140,141 -receptor hyperactivation is inherent in the cancer's natural history and is required to maintain the transformed phenotype: these cells are dependent on the persistent activity of MET for their relentless proliferation (a situation known as 'oncogene addiction') 142,143 . In this scenario, MET blockade affects a limited subset of MET downstream signals: many of the pathways controlling MET-driven responses -including STATs, JNK, p38 and NF-κB -remain active or exhibit scant responses, and only a restricted complement of Ras and PI3K transducers and transcriptional effectors is neutralized 144,145,146 .…”
Section: Met Signalling In Development and Diseasementioning
confidence: 99%
“…After the discovery of MET mutations in HRPC, studies in other solid tumors identified MET kinase domain mutations and some mutations outside the kinase domain in childhood hepatocellular carcinomas, breast cancer, colorectal cancer (CRC), head and neck squamous cell cancers (HNSCC), gastric carcinomas (GC), and cancers of unknown primary origin (CUP) (Figure 1) (13)(14)(15)(16)(17)(18)(19)(20)(21). For several years after the initial discovery, the small number of MET kinase activating mutations identified in other carcinomas suggested that mutations within the MET kinase domain were rare events in cancer.…”
Section: Met Kinase Domain Mutations In Hereditary Papillary Renal Camentioning
confidence: 99%